A novel green one-pot synthesis of biodiesel from Ricinus communis seeds by basic heterogeneous catalysis. (20th September 2018) - Martínez, Araceli; Mijangos, Gabriela E.; Romero-Ibarra, Issis C.; Hernández-Altamirano, Raúl; Mena-Cervantes, Violeta Y.; Gutiérrez, Selena
Abstract: The production of biofuels from renewable biomass resources is an attractive way to mitigate CO2 emissions and alleviate the shortage of fossil fuels. A novel green one-pot synthesis of biodiesel from Ricinus communis seeds by basic heterogeneous catalysis is reported in this work. The direct transesterification (one-step process) of the seeds with methanol in the presence of homogeneous (HCl and NaOH) or heterogeneous (Na2 ZrO3 ) catalysts was evaluated. Additionally, the comparison of the conventional (two-step process) transesterification against the direct transesterification reaction was analysed. The conventional transesterification of Ricinus communis oil with acidic (HCl/CH3 OH, 5% v/v) and basic (NaOH/CH3 OH, 5% w/w) homogeneous catalysts showed conversions of the fatty acid methyl esters (FAME) > 97% at 6 h and 3 h, respectively. Moreover, direct transesterification was carried out using a basic Na2 ZrO3 catalyst. The maximum FAME yield was 99.99% at 4 h of reaction time and 5 wt % catalyst. Finally, Green Metrics Parameters of biodiesel showed that heterogeneous direct transesterification resulted in a seven times greener synthesis compared to conventional process. This novel heterogeneous one-step process is almost ten times less hazardous than the conventional process and five times less harmful than the homogeneous one-step reaction. No n -hexane is required for oil extraction. Thus, methanol as a reactant and as a solvent increased the greenness of the heterogeneous process, and the resulting biodiesel shows good purity and composition. In addition, no water is required to purify the biodiesel. According to these results, heterogeneous direct transesterification is a promising alternative for more sustainable, cleaner and efficient biodiesel production that is crucial to developing new technologies (by chemo-selectivity). Graphical abstract: Image 1 Highlights: A green direct heterogeneous one-step process of biodiesel is proposed. Maximum yield (99.9%) with 5% of catalyst was achieved in 4 h from Ricinus communis . Methanol solvent increases the greenness of the heterogeneous process. The method is 7 times greener related to conventional one by Green Metrics Parameters.